Pelatihan Pengolahan Produk Penunjang Yang Berbasis Limbah Daun Dayu Putih Di Desa Pejarakan, Kecamatan Gerokgak Kabupaten Buleleng - Putu Herny Susanty; Nyoman Agus Trimandala; I Gede Dirga Surya Arya Widhyadanta; Ni Luh Gde Sari Dewi Astuti (CV. Multi Kreasi Media, 2024)
Pejarakan Village, located in Gerokgak District, Buleleng Regency, Bali, has great potential for developing wellness tourism-based products, particularly through the utilization of eucalyptus and herbal plants. The processing of eucalyptus in this village produces waste in the form of dry leaves and distilled water that has not been optimally utilized. Through a community service program, training was conducted to turn this waste into economically valuable body scrub products that can support the wellness tourism sector. The implementation methods involved lectures, tutorials, and discussions to educate housewives and the Women's Farming Group on the techniques of processing eucalyptus leaf waste into body scrub products. The results of this activity showed an increase in the literacy and interest of the community in processing eucalyptus waste. The evaluation indicated that 90% of the participants understood and were able to produce innovative body scrubs, positively impacting the economic welfare of the local community. This program is expected to continue with efforts to develop product marketing both online and offline to expand the market reach and enhance the welfare of the Pejarakan Village community.